Social Justice and Its Role in Mission Statements: Voicing Commitments to Social Justice and Implications for Student Affairs Professionals - Brittany Devies; Valerie Arias; Olivia F. Brown; Ellie J. Foreman (Ali Khorsandi Taskoh, 2023)
Upon reviewing the mission statements of over 6,500 institutions of higher education in the United States, 40 institutions were isolated for their inclusion of the words "social justice." The research team analyzed the use of the term through qualitative content analysis. In this conventional content analysis, open, inductive coding was used to explore how social justice is included in mission statements and its relevant context. Using content analysis, the research team developed a framework of four value types present in mission statements: foundational values, espoused values, instilled values, and pursued values. The findings explore what each of these values mean for practice. Finally, we conclude with implications for practice, specifically for new professionals and institutions engaging in this work. As new professionals enter the student affairs profession, these implications for practice can help them understand how their personal values and pursuits for social justice fit into their institution's mission statements and actions taken for social justice.